The Invisible Forces That Create the Health of Populations: A Public Health of Consequence, April 2018 - Galea, Sandro; Vaughan, Roger D. (American journal of public health (1971), 2018)
The HPV vaccine is one of the truly breakthrough medical innovations of the past two decades, building on a Nobel prize-winning discovery about the role of HPV in carcinogenesis.2 The introduction of the HPV vaccine broadly across the country can therefore stand to reduce the incidence and burden of a number of cancers. [...]the mere introduction of the vaccine falls far short of delivery of the vaccine, and in the particular case of vaccinations, population penetrance of vaccination is central to their broader effectiveness. [...]it is both not surprising and yet instructive to the larger narrative that a range of policies all contribute to the widespread delivery of HPV vaccine and its broader effectiveness. Medicaid expansion is inextricably linked to the national discussion around health insurance and the Affordable Care Act, and school-entry requirements and classroom sex-education mandates are frequently politicized and subject to charged cultural conversations.